Gamma spectrometric analysis of lower Danube samples from Romania - Pojar Vintila Iulian; Ujeniuc Sorin; Catianis Irina; Alexandrescu Bogdan; Scrieciu Albert M.; Vasilca Silvana; Suvaila Rares (Nuclear Technology and Radiation Protection)
This paper focuses on the natural and anthropogenic radioactivity of sediment samples from key spots located in the Lower Danube area and the Danube Delta region. The idea of the study is to confirm that gamma spectrometry is an efficient method for geological sample characterization in terms of isotopic ratios and also for evaluating the impact of nuclear activi- ties, namely testing artificial contamination. This is a preliminary study meant to analyze the relevance of a database for reference sediments from the Danube River built via gamma ray spectrometry.